Telomere Length in Idiopathic Recurrent Pregnancy Loss - Onat, Taylan; Çaltekin, Melike Demir; Inandiklioglu, Nihal; Baser, Emre; Kirmizi, Demet Aydogan; Kara, Mustafa; Ercan, Fedi; Yalvac, Ethem Serdar (Zeitschrift für Geburtshilfe und Neonatologie, 2021)
Objective Telomere length is used as an indicator of biological aging. It is well known that one of the most remarkable risk factors of recurrent pregnancy losses is advanced maternal age. The objective of this study was to investigate the correlation between idiopathic recurrent pregnancy loss and telomere length.Method The study group included 40 women, while the control group consisted of 41 healthy women whose age and body mass index were matched. A venous blood sample was taken from all participants into EDTA tubes in the early follicular phase, and telomere length was measured through the qPCR technique.Results When the mean TL of the groups was compared, it was determined that TL was significantly shorter among the iRPL group (7763.89±924.58 base pair) compared to the control group (8398.84±1102.95 base pair) (p<0.006). Whereas FSH and E2 were higher in the iRPL group, TAFC was lower (p<0.001). When the correlation between telomere length and endocrine parameters was statistically tested in the iRPL group, a negative correlation was found between FSH and telomere length (r=-0.437; p<0.001).Conclusion Shortened telomere length might play a role in the etiology of iRPL. We are of the opinion that patients with RPL should be screened for the presence of cardiovascular diseases and other chronic diseases, as is the case for POF.
Keywords: Recurrent pregnancy loss; Telomere length; Biological age